Educação gerencial e avaliação de desempenho: um estudo sobre a política educacional do modelo de gestão todos por Pernambuco (2007-2016) - Moura, Sérgio Andrade de (2017)
This research aims to investigate the education policy of Pernambuco, focusing especially on the Integral Education Program and the educational performance evaluation policy, within the political, managerial and neoliberal context of the management model All for Pernambuco. The study was developed through a methodological proposal based on a bibliographical and documentary research. This research was based on the theoretical-methodological framework of the Policy Cycle Approach (BALL, GOLD, 1992), with the use of the first two contexts of the original framework, i.e the context of influence and the context of the production of text. In addition, it was used as tools to subsidize the contextualization of educational policies, managerialism and peformativity (BALL, 2001; 2004; 2005). Based on this study, in relation to the educational policies of the Management Model All in Pernambuco, new forms of educational management guided by the managerial and neoliberal assumptions were verified. Specifically, in relation to the Integral Education Program, instituted by the All Management Model by Pernambuco, it was identified that this program adopts a managerial model of education focused on results, above all, regarding the goals of the IDEB and IDEPE. The evidence also pointed out that it is crossed by the presuppositions present in the Theory of Human Capital, that is, the formation of a suitable worker to promote economic development and satisfy the imperatives of capital accumulation. Regarding the policy of evaluation of educational performance, we verified the “implementation” of vertical evaluation models, focused on performance and crossed by accountability, meritocracy and performativity, where only the growth of the standardized large scale SAEPE/SAEB/PISA) and the achievement of the goals (IDEPE / IDEB) guarantee a “quality” education.